Assessing the Effectiveness of Solution-Focused Brief Therapy for Couples Raising a Child with Autism: A Pilot Clinical Outcome Study. Issue 3 (3rd July 2019) - Turns, Brie; Jordan, Sara Smock; Callahan, Kevin; Whiting, Jason; Springer, Nicole Piland
Abstract: The increased diagnostic rates and awareness of autism spectrum disorders (ASD) have led to more couples with children on the spectrum seeking professional services. Parents with a child with ASD have reported higher levels of marital dissatisfaction and parental stress than couples raising a child with other developmental disabilities. Unfortunately, there is a lack of research investigating the effectiveness of treatments for couples raising a child with ASD. In this pilot clinical outcome study, a multiple baseline design was used to identify the effectiveness of solution-focused brief therapy for couples raising a child with ASD.